Recurrent hormone treatment alters growth, haematology, and gonadal maturation in the endangered spiny eel (Mastacembelus armatus) : Effects of recurrent hormone treatment in Mastacembelus armatus - Talukder , Sadman; Akter, Faria; Mazumder, Sabuj Kanti; Ahsan, Md Emranul; Rahman, Mohammad Lutfar (Annals of Bangladesh Agriculture, 2026)
The freshwater Spiny eel (Mastacembelus armatus) is an endangered species native to South and Southeast Asia, with declining populations due to habitat degradation and reproductive failure in captivity. This study evaluated the effects of repetitive hormone treatment using Compound S-GnRHa on the growth performance, hematological parameters, and gonadal development of M. armatus over a 90-day experimental period. Sixty wild-captured fish were divided into hormone-treated and control groups, with the hormone group receiving intramuscular injections at 20-day intervals. Results showed that repeated hormone injections significantly enhanced the gonadosomatic index (GSI) and fecundity (1865.66 ± 230.22 eggs), while fish in control group failed to reach full sexual maturity. Histological analysis revealed progressive oocyte development from early perinucleolar stages to final maturation in females, and advanced stages of spermatogenesis in males from the hormone-treated group. However, hormone treatment negatively affected somatic growth and induced hematological instability, reflected by reduced red blood cell (RBC) and white blood cell (WBC) counts, hemoglobin, and cholesterol levels. Despite its effectiveness in promoting reproductive maturation, repetitive hormone administration may generate physiological stress and growth suppression. These findings demonstrate that synthetic gonadotropin-releasing hormone analog (S-GnRHa) stimulation holds promise for ex-situ breeding programs while underscoring the importance of minimizing trade offs between maturation and health. Further studies should focus on optimizing hormone dosages, reducing stress through environmental enrichment, and exploring alternative maturation induction methods to support conservation and aquaculture of the endangered spiny eel. Ann. Bangladesh Agric. 29(2): 111-124